Dietary lysine affects growth performance, whole‐body composition and growth‐related gene expression in the yellow drum Nibea albiflora. (28th August 2020) - Wang, Ligai; Zhao, Dan; Tan, Peng; Chen, Ruiyi; Xu, Dongdong
Abstract: Excess and deficient dietary lysine intake can have negative impacts on fish growth, emphasizing the importance of developing species‐specific formulations. A 50‐day feeding experiment was conducted to evaluate the optimal dietary l ‐lysine demand for juvenile Nibea albiflora . Fish were fed six diets, in which the l ‐lysine content was 13.1, 18.1, 23.1, 28.1, 33.1 and 38.1 g/kg dry diet (measured values). The 18.1–33.1 g/kg diets significantly enhanced weight gain and specific growth rate. Similarly, feed efficiency was highest in fish fed the 23.1 and 33.1 g/kg diets. The protein efficiency ratio of fish fed 13.1 g/kg diet was significantly lower than those of fish fed 23.1, 28.1 and 33.1 g/kg diets. The 28.1 g/kg diet resulted in higher whole‐body protein content than other diets. The expression level IGF‐I and IGF‐IR in liver and muscle significantly increased by proper dietary lysine, respectively. Based on a second‐order polynomial model of weight gain, the optimal demand of l ‐lysine in the diet for juvenile N. albiflora is 24.85 g/kg diet. These results have practical implications for improving growth performance and feed utilization in juvenile N. albiflora .